Manajemen Kepemimpinan Kepala Madrasah Sebagai Supervisor Dalam Meningkatkan Kinerja Guru Di Madrasah Ibtidaiyah Negeri 2 Karimun - Sumarno Sumarno; Azrizanudi Azrizanudi; Hikmatul Hidayah (Institut Agama Islam Hidayatullah Batam, 2026)
This study aims to analyze the leadership management of the school principal as supervisor in improving teacher performance at Madrasah Ibtidaiyah Negeri (MIN) 2 Karimun, Riau Islands Province, Indonesia. Employing a descriptive qualitative approach with a single-case study design, data were collected through in-depth semi-structured interviews, classroom observations, and document analysis involving the principal and four purposively selected teacher informants during the 2024/2025 academic year. Thematic analysis reveals that the principal implements four structured supervision stages: (1) systematic and participatory program planning involving senior teachers; (2) supervision through classroom visits with a collegial-humanistic approach; (3) reflective individual evaluation based on written observation records; and (4) multi-programmatic follow-up activities including MGMP sessions, question-item training, motivation seminars, and digital literacy webinars. Supporting factors include adequate school facilities, teacher enthusiasm, and a strong collegial culture, while constraining factors involve the principal's dense administrative schedule, limited budget allocation, and supervision frequency of only once per year. These findings affirm the critical need to increase supervision frequency and integrate digital-based supervision to optimize madrasah teacher performance in the 21st-century education era.